2000
DOI: 10.1001/archpsyc.57.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Low Salivary Cortisol and Persistent Aggression in Boys Referred for Disruptive Behavior

Abstract: Background: Persistent antisocial behavior in adulthood is often preceded by childhood-onset aggressive conduct disorder. Aggressive syndromes in both children and adults have previously been associated with abnormalities in peripheral responses to stress. One peripheral measure, salivary cortisol concentration, may reflect individual differences in the hypothalamic-pituitary-adrenal axis that underlie propensities for aggression, socialization, and adaptation to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
280
5
15

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(320 citation statements)
references
References 27 publications
20
280
5
15
Order By: Relevance
“…The finding of low post-awakening cortisol levels in the DP + subgroup are in line with other studies that have found low cortisol levels in antisocial children (McBurnett et al, 2000;Pajer et al, 2001;Tennes et al, 1986;Tennes and Kreye, 1985). Notably, low cortisol levels were only observed in the first hour after awakening, whereas during the rest of the day the levels were not significantly different between groups, emphasizing the need for repetitive cortisol sampling over the day in future studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding of low post-awakening cortisol levels in the DP + subgroup are in line with other studies that have found low cortisol levels in antisocial children (McBurnett et al, 2000;Pajer et al, 2001;Tennes et al, 1986;Tennes and Kreye, 1985). Notably, low cortisol levels were only observed in the first hour after awakening, whereas during the rest of the day the levels were not significantly different between groups, emphasizing the need for repetitive cortisol sampling over the day in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies in minors demonstrated low cortisol levels in resting conditions to be associated with antisocial behavior (Pajer et al, 2001;McBurnett et al, 2000;Tennes et al, 1986;Tennes and Kreye, 1985), whereas others did not report a significant relationship (Azar et al, 2004;Schulz et al, 1997;Kruesi et al, 1989;Scerbo and Kolko, 1994;Klimes-Dougan et al, 2001;Stoff et al, 1992). In a recent longitudinal study, low cortisol levels in preadolescence were found to be associated with low harm avoidance, low self-control, and more aggressive behavior when reaching middle adolescence 5 years later (Shoal et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The evidence for corticosteroid effects on behavior in other vertebrates is contradictory. In humans, low salivary cortisol has been associated with persistent aggression (McBurnett, Lahey, Rathouz and Loeber, 2000) while in domestic pigs and the blue-footed booby (Sual nebouxii) elevated cortisol and corticosterone have been suggested to facilitate submissive behavior during aggressive interactions (Fernandez, Meuniersalaun and Mormede, 1994;de la Mora, Drummond and Wingfield, 1996) and similarly, administration of corticosterone to the blotched lizard (Uta stansburiana) reportedly reduces aggression (De Nardo and Licht, 1993). However, in contrast to these reports, which indicate a reasonable consistency in the effects of corticosteroids on behavior, no correlation between aggressiveness and plasma corticosterone responsiveness to stressors was reported for rats (Sgoifo, de Boer, Haller and Koolhaas, 1996) and the administration of corticosterone to rats had variable behavioral effects which were dependent on context and experience (Haller, Albert and Makara, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased cortisol levels have been associated with antisocial behavior in girls, 22 and early-onset aggression in boys. 21 Taken together, these data suggest that variations in the mu-opioid receptor gene might provide a common link between certain forms of aggression and HPA axis function.…”
mentioning
confidence: 85%
“…21,22 An inverse relationship between plasma cortisol levels and offensive aggressive behavior in adolescent male rhesus monkeys 20 is mirrored in humans. Decreased cortisol levels have been associated with antisocial behavior in girls, 22 and early-onset aggression in boys.…”
mentioning
confidence: 99%